Multifunctional PVA/PANI Aerogels Featuring Dendritic Arm for Enhanced Tunable Microwave Absorption Property - Ji, Qianhe; Liu, Deyun; Liu, Shuai; Xu, Lei; Zhu, Yaofeng; Wang, Hui‐Ya (Polymer engineering and science, 2025)
ABSTRACT Designing electromagnetic wave‐absorbing materials (EMAs) with adjustable performance is crucial for adapting to constantly changing electromagnetic environments. Herein, a flexible polyvinyl alcohol/polyaniline (PPA) aerogel was fabricated through a one‐step process combining unidirectional freezing and low‐temperature polymerization. During this process, polyaniline (PANI) self‐assembles into a “coral‐like” nanostructure, which promotes the formation of secondary dendritic arms. These secondary dendritic arms are beneficial for enhancing wave absorption by improving the conductive network and heterogeneous interfaces. Consequently, the PPA aerogel achieves a minimum reflection loss (RLmin) of −26.85 dB and covers an effective absorption bandwidth (EAB) of 3.08 GHz (9.33–12.04 GHz) at a thickness of 3.8 mm. Additionally, the electromagnetic parameters can be dynamically tuned by adjusting the pore structure and conductive network through compression, enabling the control of wave‐absorbing performance. Furthermore, the high porosity of the aerogel limits convective heat transfer and reduces thermal radiation, which imparts excellent thermal insulation and infrared stealth. This work offers valuable guidance for developing multifunctional EMAs with adjustable absorption characteristics.